Development and Feasibility Study of a Telemedicine Tool for All Patients with IBD: MyIBDcoach. Issue 4 (6th March 2017) - de Jong, Marin; van der Meulen-de Jong, Andrea; Romberg-Camps, Mariëlle; Degens, Juliette; Becx, Marco; Markus, Tineke; Tomlow, Henny; Cilissen, Mia; Ipenburg, Nienke; Verwey, Marthe; Colautti-Duijsens, Laurence; Hameeteman, Wim; et al.
Abstract : Background: Tight control of disease activity, medication side effects, and adherence are crucial to prevent disease complications and improve quality of life in patients with inflammatory bowel disease (IBD). The chronic nature and increasing incidence of IBD demand health care innovations to guarantee future high-quality care. Previous research proved that integrated care by telemedicine can improve outcomes of chronic diseases. Currently available IBD telemedicine tools focus on specific patient subgroups. Therefore, we aimed to (1) develop a telemedicine system suitable for all patients with IBD in everyday practice and (2) to test this system's feasibility. Methods: With a structured iterative process between patients, dietitians, IBD nurse-specialists, and gastroenterologists, myIBDcoach was developed. During 3 months, myIBDcoach's feasibility was tested by 30 consecutive outpatients with IBD of 3 hospitals. Thereafter, patients and health care providers completed a questionnaire covering satisfaction, accessibility, and experiences with myIBDcoach. Results: MyIBDcoach enables continuous home-monitoring of patients with IBD and optimizes disease knowledge and communication between patients and health care providers. Besides disease activity, medication adherence, and side effects, myIBDcoach monitors malnutrition, smoking, quality of life, fatigue, life-events, work participation, stress, and anxiety and depression and provides e-learnings for patient empowerment. Patients graded the system with a mean of 7.8 of 10, and 93% would recommend myIBDcoach to other patients. Conclusions: We developed myIBDcoach, which enables integrated care for all patients with IBD, regardless of disease severity or medication use. The feasibility study showed high satisfaction and compliance of patients and health care providers. To study myIBDcoach's efficacy, a multicenter randomized controlled trial has been initiated.